Ear-related problems among children attending the paediatric and otorhinolaryngology out-patients clinics of the University of Nigeria Teaching Hospital, Enugu - Ilechukwu, GC (Afr Health Sci, 2016)
BACKGROUND: Ear related diseases are commonly seen in clinics worldwide especially among children. They are associated with significant morbidity and frequent hospital visits. Limited data exists regarding the burden of ear disease among Nigerian children. OBJECTIVE: To determine the prevalence of ear-related problems among children presenting at the Paediatric and Otorhinolaryngology clinics of the University of Nigeria Teaching Hospital, Enugu. MATERIALS AND METHODS: This was a cross-sectional study conducted at the Paediatric and Otorhinolaryngology Clinics of the University of Nigeria Teaching Hospital Enugu. All children aged 0 and 17 years presenting between 1(st) June and 31(st) August 2006 with ear-related problems were enrolled consecutively into the study. Data analysis was by SPSS version 11. RESULTS: Three thousand and twenty-one children were seen during the study period. Out of these, 248 children (8.2%) presented with ear-related problems. Chronic otitis media (30.5%), acute otitis media (29.9%), cerumen auris (11.3%), otitis externa (10.1%), hearing impairment (7.3%) and foreign body in the ear (5.7%) were the most commonly diagnosed ear-related problems. CONCLUSION: Ear-related problems among children presenting at the UNTH Enugu were not uncommon. However, otitis media was the most commonly diagnosed ailment affecting the ears in children.